Stratigraphic range of the large canids (Carnivora, Canidae) in South America, and its relevance to quaternary biostratigraphy - Prevosti, Francisco Juan (2009)
The fossil record of large canids is reviewed in order to improve the current South American biostratigraphic chart. This analysis is based on the recent systematic revision of those taxa performed by one of the authors and new field and paleomagnetic works. The first occurrences of large canids are limited to the Early–Middle Pleistocene (Ensenadan stage/age). Theriodictis platensis, “Canis” gezi, and Protocyon scagliorum are restricted to the Ensenadan. Most T. platensis specimens came from late Ensenadan levels (0.78–≈0.5 Ma), but the oldest one is between 0.78 Ma and 1 Ma old. The biochron of Protocyon troglodytes spans the Ensenadan–Lujanian interval, and its youngest remains are associated with 14C dates of 25–27/20–10 ka BP. Most individuals of Protocyon tarijensis could be between 1 Ma and 10 ka, but one specimen comes from a level surely younger than 0.78 Ma, and probably younger than 28 ka. The oldest records of the living species Chrysocyon brachyurus are between ca. 0.3 Ma–9 ka BP. The first record of Canis dirus (and Canis by extension) in South America is limited to the latest Pleistocene (<25–27 ka).